THE USED OF RAG AS MEDIA OF CATON PUPPET ART WORK WITH KOLASE TECHNIQUE IN LEARNING SKILL ART FOR THE STUDENTS OF ELEVENTH GRADER OF BINA BANGSA KERSNA VOCATION HIGH SCHOOL. - Azmi, Fauziah Ulul (Eduarts: Jurnal Pendidikan Seni, 2017)
Generally, puppet art work needs a lot of money an equipments so that it’s impossible to be implemented in schools. In order to implement puppet in schools, the researcher used carton and rag as alternative media in puppet art work. The aim of the study is to describe, analyze identify, rag as coloring media of the puppet. The method used in this study is development research wich is done trough restrained observation. The collection of the data was done by observation, interview and documentation. The learning method used demonstrative, discussion and giving assignment method. The learning strategy wich is used is scientific approach. The data analysis was done by reduction, presentation, an verification of the data. The result of the student’s art work at the aspect of creativity wich got good score were 18 students of 56,25%, 13 students or 40,62% students were categorized very good score and enough category is a student or 3,12%. At the aspect of visual quality of the art work, there were 14 students or 43,75% got good category, 6 students or 18,75% got very good category, and 12 students or 37,5% of students got enough category. At the aspect of mastering the technique and procedure, 15 students or 46,87% were categorized as very good, and a studnt or 3,12% of student was categorized as enough.